ECO-COSMOLOGY: PENDAMPINGAN MASYARAKAT TENGGER DALAM MENJAGA KESEIMBANGAN ALAM - Koesbardiati, Toetik; Murti, Delta Bayu; Furinawati, Yunita; Suhanti, Indah; Wibowo, Nimas (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: This community service aims to provide insight to the Tengger community in their efforts to protect nature which is starting to be threatened by the development of the tourism industry. This assistance is centered on understanding how a ritual ceremony, in this case focusing on unan-unan, can become a fortress for society in facing modernization and tourism. Methods: Qualitative methods are used in the data collection process. Data was collected through interviews with selected informants, namely informal and formal leaders and other informants who were considered to know Unan-Unan. Furthermore, all of this data is analyzed and disseminated to the community through introductions to the problems currently being faced. The introduction is carried out by explaining all forms of risks that may arise when tourism continues to develop and could threaten their natural environment. Results: This assistance offers an eco-cosmology perspective which is considered capable of explaining the benefits of deep unan-unan rituals involving the three concepts of life (Tri Hita Karana). Furthermore, this assistance is also able to provide insight into the Tengger community in protecting the environment by restoring their sacred areas